Análise econômica da produção de biodiesel para a agricultura familiar no município de Corbélia-PR - Borsoi, Augustinho (2012)
This study aimed to assess the economic feasibility of biodiesel production in an associative form by family farmers from the municipality of Corbélia-PR. Biodiesel has proven to be a socio-economic and environmental alternative for the partial or total substitution of diesel oil due to its similar physicochemical characteristics. In Brazil, the biodiesel has great social appeal by the utilization of raw material that comes from family agriculture. However, the participation of family farmers acting directly in the transformation of vegetal oil into biodiesel still requires studies concerning to its economic feasibility. The present work was developed by means of a simulation, in order to verify the economic feasibility of the installation of a biodiesel plant able to produce 1000 L day-1 by family farmers. The raw material used for the extraction of oil were soy, sunflower, and canola, in the summer and winter crops, once that pies made of these oilseeds can be used to feed cattle. Cash flow, with expenses (output) and revenue (input) before and after the installation of the plant were elaborated. From the cash flow, it was possible to perform the economical analysis, by using the following as indicators: Net present value (NPV), Internal rate of return (IRR) and Payback period. The IRR for the project was 43%, the NPV was R$ 92,049.96 and the payback was 2.57 years. Based on these indicators, one can conclude that the production of biodiesel in association by the family farmers showed economic feasibility. It is also relevant to highlight the importance of interaction among the property s activities, by using pies to feed the cattle.